IMPLEMENTASI PERATURAN DAERAH NOMOR 3 TAHUN 2017 TENTANG KAWASAN TANPA ROKOK (KTR) DI SEKOLAH MENENGAH KEJURUAN (SMK) PADA WILAYAH KERJA PUSKESMAS KEBUN KOPI KOTA JAMBI - Faza Jirati Zajra; Arnild Augina Mekarisce; Usi Lanita; Rumita Ena Sari (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2026)
Smoking prevalence in Indonesia remains high, particularly among adolescents aged 15–19 years, making schools a strategic setting for tobacco control. This descriptive qualitative study explored KTR policy implementation using George C. Edward III’s framework of communication, resources, disposition, and bureaucratic structure. Data were collected through in-depth interviews with 17 informants, including school principals, teachers, UKS supervisors, students, security officers, and canteen vendors. Implementation of the KTR policy was not yet optimal. Communication focused mainly on students and lacked explanation of the policy’s legal basis. Resource limitations included the absence of a dedicated KTR team, training, specific budget allocation, and evenly distributed information media. Disposition-related issues were reflected in continued smoking by some school personnel. Bureaucratic structure weaknesses included the absence of a specific SOP and formal KTR organizational structure. Strengthening institutional support, resources, supervision, and intersectoral coordination is essential to improve KTR implementation in schools.